Clinical characteristics, risk factors and angiographic profile of acute coronary syndrome patients in a tertiary care center of Nepal.
Background and Aims: Acute coronary syndrome (ACS) refers to a group of clinical symptoms consistent with new onset or worsening ischemic symptoms. ST-elevation myocardial infarction (STEMI), non-ST elevation myocardial infarction (NSTEMI) and unstable angina (UA) are the three types of ACS. The objectives were to study the risk factors prevalence, angiographic distribution and severity of coronary artery stenosis in ACS among patients admitted in Cardiology Department of Manmohan Cardiothoracic Vascular and Transplant Center (MCVTC). Methods: This is a restrospective study of 419 ACS patients admitted and treated in MCVTC from November 2017 to October 2018. Patients were divided into STEMI, NSTEMI and UA then analyzed for various risk factors, angiographic patterns and severity of coronary artery disease. Results: Mean age of presentation was 59.3Å